Research Trends in Peace Education as A Pillar in Creating A Safe and Comfortable Learning Environment: A Bibliometric Study - Anif Istianah; Cecep Darmawan; Dadang Sundawa; Susan Fitriasari; Amjad Shamim (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Diversity is inevitable in every community, including the school environment. By weaving diversity together, schools can create safe, respectful, and supportive spaces, allowing every student to feel accepted and valued. This study examines trends in peace education research as a pillar for creating safe and comfortable learning environments. Method: Using bibliometric analysis, the study reviews data from the Scopus database covering the period from 2019 to 2024, with keywords such as "peace education," "harmonious education," and "civilized education ."Results: The analysis of the Scopus database from 2019 to 2024 shows an increasing recognition of the role of peace education in character-building and promoting inclusive education practices. The findings reveal that the United States is the primary contributor to peace education research, with significant contributions from institutions such as the University of Cambridge and the University of KwaZulu-Natal. Further analysis identifies several key themes in this research, including the integration of peace values into the curriculum, addressing socio-cultural challenges, and efforts to promote tolerance and mutual respect in school environments. Novelty: This study contributes to understanding trends, collaboration opportunities, and policy implications to enhance peace education and create globally harmonious learning environments.